2016
DOI: 10.18632/oncotarget.7458
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in PRDM8 is indicative for dyskeratosis congenita

Abstract: Dyskeratosis congenita (DKC) is associated with impaired telomere maintenance and with clinical features of premature aging. In this study, we analysed global DNA methylation (DNAm) profiles of DKC patients. Age-associated DNAm changes were not generally accelerated in DKC, but there were significant differences to DNAm patterns of healthy controls, particularly in CpG sites related to an internal promoter region of PR domain containing 8 (PRDM8). Notably, the same genomic region was also hypermethylated in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 48 publications
8
24
0
2
Order By: Relevance
“…However, no significant results were found (data not shown). In addition, previous works reported that reduced expression of PRDM8 was caused by hypermethylation in patients with dyskeratosis congenital, aplastic anemia, and Down syndrome . Based on our results, down‐regulated PRDM8 expression in HCC cell lines was not significantly restored by treatment with 5‐aza‐2′‐deoxycytidine (data not shown).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…However, no significant results were found (data not shown). In addition, previous works reported that reduced expression of PRDM8 was caused by hypermethylation in patients with dyskeratosis congenital, aplastic anemia, and Down syndrome . Based on our results, down‐regulated PRDM8 expression in HCC cell lines was not significantly restored by treatment with 5‐aza‐2′‐deoxycytidine (data not shown).…”
Section: Resultssupporting
confidence: 57%
“…It is also possible that HES5 might be an upstream regulator of PRDM8. Aberrant hypermethylation of PRDM8 is observed in dyskeratosis congenital, aplastic anemia, Down syndrome, and Werner syndrome . PRDM8 has hypomethylated CpG islands in endometrial cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants/heterozygous mutations in telomere maintenance genes were screened using a self-designed panel containing the entire coding sequences for CTC1, DKC1, NHP2, NOP10, RTEL1, TERC, TERT, TCAB1, USB1, and exon 6 of TINF2. 20,21 Flow-FISH Vital sterile frozen MNC from PB was used for the flow-FISH analysis of TL, as previously described. [22][23][24][25][26] Briefly, samples were prepared for cell denaturation and mixed with an FITC-labeled telomere-specific (CCCTAA)3-peptide nucleic acid FISH probe (Eurogentec, Liège, Belgium) for DNA hybridization followed by DNA counterstaining with LDS 751 (Sigma).…”
Section: Patientsmentioning
confidence: 99%
“…Des Weiteren ist eine Defizienz der Poly(A)‐spezifischen Ribonuklease, welche die Poly(A)‐Schwänze der mRNA kürzt und daher zum Silencing führt, mit Dyskeratosis congenita assoziiert, wobei Enzym‐depletierte Zellen einen niedrigen Gehalt spezifischer Ribonukleinsäuren aufweisen, die essenziell für die Aufrechterhaltung des Telomerase‐Komplexes sind . Die Telomerlänge scheint außerdem mit der Methylierung der Subtelomere assoziiert zu sein .…”
Section: Molekulare Aspekteunclassified